2019
DOI: 10.1111/jcpt.12796
|View full text |Cite
|
Sign up to set email alerts
|

An 11-year retrospective review of cyproheptadine use in serotonin syndrome cases reported to the California Poison Control System

Abstract: Summary What is known Cyproheptadine is a serotonin and histamine antagonist that has been suggested as a treatment for serotonin syndrome in case reports. Objective We sought to examine the differences between outcomes and treatment recommendations in patients who received and did not receive cyproheptadine for a probable serotonin syndrome. Methods A retrospective review of cases reported to the California Poison Control System between 2006 and 2017 involving cyproheptadine administration or consideration fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(13 citation statements)
references
References 17 publications
0
11
0
1
Order By: Relevance
“…Furthermore, doxepin may act as a nonselective serotonin receptor/reuptake inhibitor for the serotonin transporter [5]. Another beneficial effect of a strong serotonin antagonist such as doxepin is that it may counteract the most serious, even lethal, side effects of some antidepressants (e.g., serotonin syndrome, which has a ≤5.9% mortality rate), particularly when administered alongside serotonin reuptake inhibitors to treat mental disorders [6].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, doxepin may act as a nonselective serotonin receptor/reuptake inhibitor for the serotonin transporter [5]. Another beneficial effect of a strong serotonin antagonist such as doxepin is that it may counteract the most serious, even lethal, side effects of some antidepressants (e.g., serotonin syndrome, which has a ≤5.9% mortality rate), particularly when administered alongside serotonin reuptake inhibitors to treat mental disorders [6].…”
Section: Introductionmentioning
confidence: 99%
“…In a recent systematic review, cyproheptadine use was reported to be 16% among 56 SS patients with a mean age of 42 24 . In contrast, in another previous study, 23% of 288 patients (mean age 49.7) were treated with cyproheptadine and reported no benefit for worse outcomes of SS in patient populations, concluding that the use of cyproheptadine is questionable 26 . Accordingly, in this study, 37% of patients with SS received cyproheptadine more frequently than in previous reports, and this might be the reason why none of our patients progressed severely.…”
Section: Discussionmentioning
confidence: 93%
“…Other AEs were more rarely reported. When cyproheptadine was used to treat serotonine syndrome, it was generally well-tolerated and efficient, although tachycardia, sedation, hyperthermia, delirium, urinary retention, dilated pupils, decreased bowel movements, dry mouth and dry skin were described ( 31 ). No dermatologic or haematologic AEs were reported.…”
Section: Resultsmentioning
confidence: 99%